Evidence-based geriatric nursing protocols for best practice - Boltz, Marie (Springer Pub. Co., 2012)
One of the premier reference books for geriatric nurses in hospital, long-term, and community settings, this 4th edition has been thoroughly updated to provide the most current, evidence-based protocols for care of common clinical conditions and issues in elderly patients. Designed to improve the quality, outcomes, and cost-effectiveness of health care, these guidelines are the result of collaboration between leading practitioners and educators in geriatric nursing and New York University College of Nursing. Protocols for each clinical condition have been developed by experts in that particular area, and most have been systematically tested by over 300 participating hospitals in "Nurses Improving Care for Health System Elders" (NICHE). Evidence is derived from all levels of care, including community, primary, and long-term care. A systematic method in compliance with the AGREE appraisal process was used to rate the levels of evidence for each protocol. Protocols are organized in a consistent format for ease of use, and each includes an overview, evidence-based assessment and intervention strategies, and an illustrative case study with discussion. Additionally, each protocol is embedded within chapter text, which provides the context and detailed evidence for the protocol. Each chapter contains resources for further study